Prevalence of acute morbidities and their health seeking behaviour among under-five children of urban slums in a city in Karnataka - B. N., Yamuna; K., Ratnaprabha G.; Kengnal, Prakash (International Journal Of Community Medicine And Public Health, 2017)
Background: Morbidity and lack of health facility especially in the first five years of life would cause irreparable damage. Therefore it is important to assess the magnitude of morbidities, and their health seeking behaviour. The objectives of the study were to assess the prevalence of acute morbidities and their associated factors among Under-five (U5) children residing in slums of Davanagere city, Karnataka, and to assess the health-seeking behaviour of their mothers/caregivers Methods: It was a cross sectional study done in the slums of Davanagere city during August-September 2016. Using 30 cluster sampling technique, the estimated sample size was 656. A total of 22 children were included in each cluster. Questionnaire consisting of demographic details, history of acute morbidities in the past two weeks and their treatment details was administered to the mother/caregiver. Data was entered in Microsoft Excel sheet and analyzed using SPSS Version 20. Results: Totally 656 mothers/caregivers of U5 children were contacted, majority of the children were in the age group of 13 to 60 months. Total of 348 (53%) children suffered from some acute morbidity in the past 2 weeks, of whom 282 (81%) children were taken to some health care facility, and majority preferred private practitioner (73.4%). Most common reason for poor health seeking behaviour was “following the medicines which were prescribed for previous illness”. Conclusions: More than half of the children suffered from some acute morbidity in the past 2 weeks and 81% of them were taken to health care facility.